Concentration of Astragalus Polysaccharide by Polysulfone-Activated Carbon Modified with Nitric Acid Blend Ultrafiltration Membranes - Dan-Dan, Hao; Jian-Qiu, Chen; Xin-Qiao, Liao; Yan, Zheng; Yi-Bing, Ji (Journal of Membrane and Separation Technology, 2013)
In this study, Astragalus polysaccharides were concentrated by ultrafiltation membranes prepared by blending polysulfone (PSF) with activated carbon modified with nitric acid(HAC) by immersion precipitation phase inversion method. Water flux and retention to bovine serum albumin of the membranes were investigated. The morphology of membranes were also observed by scanning electron microscopy (SEM). In order to obtain best concentration performance, effects of operating pressure, feeding temperature, operating time, feeding concentration and pH value on concentration and extraction of astragalus polysaccharide were studied. The best conditions for concentration were as follows: operating pressure is 0.4 MPa, feeding temperature is 25 °C, feeding concentration is 1 g·L-1, pH value is neutral. Under these conditions, the ultrafiltration membrane flux was 62.6 L·m-2·h-1, the retention to astragalus polysaccharide was 91.2%, and the attenuation rate of water flux was 12.5% in one hour.